Adaptive Regulation and Partial Failure Recovery of Immune Network - Lou Jianan; Li Yang; Xiefang Fang; Yujian Hua (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In order to solve the problem that taking network reconfiguration when the circuit is partial failure leads to a waste of computing resources and long repair time, the article proposes a way to limite the failure influence in a local scope through adaptively regulating the immune network . On the basis reviewing of immune network theory, a immune network structured representation method is raised. In order to make the immune network have fault tolerant ability, adaptively adjusting the structure of the immune network can dynamically chang the immune network function. Lastly, a partial failure recovery experiment of the motor control circuits is applied to test the performance of immune network adaptive regulation. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2858